Synthesis and antitumour activity of arctigenin amino acid ester derivatives against H22 hepatocellular carcinoma. Issue 4 (16th February 2018) - Cai, Enbo; Guo, Shijie; Yang, Limin; Han, Mei; Xia, Jing; Zhao, Yan; Gao, Xiaorui; Wang, Yu
Abstract: Arctigenin (ARG) is famous in its abundant pharmacological activity. However, many researches in it entered the bottleneck period because of its poor water solubility. The derivatives of ARG have been synthesised with five amino acids which have t -Butyloxy carbonyl (BOC) as a protective group. We examined the effects of removing BOC. The results showed that the amino acid derivatives without protective group have better water solubility and nitrite-clearing ability than ARG. Based on these results, ARG6′ and ARG9′ were selected at a dosage of 40 mg/kg to evaluate their antitumour activity. The percentage inhibition rate of ARG6′ and ARG9′ were 55.87 and 51.40, respectively, which was twice as much as ARG. Furthermore, they could increase liver and kidney indexes and produce less damage in these organs. In brief, this study provides a basis for new drug development. Abstract :